1973
DOI: 10.1029/ja078i025p05524
|View full text |Cite
|
Sign up to set email alerts
|

Periodically structured Pc 1 micropulsations during the recovery phase of intense magnetic storms

Abstract: The occurrence of periodically structured Pc 1 (pPc 1) during several intense geomagnetic storms is examined in detail. Unlike unstructured or quasi‐structured Pc 1, pPc 1 strongly tend to occur only during a later epoch of the recovery phase of geomagnetic storms. The available pPc 1 data, together with satellite and ionospheric data, are consistent with the idea that pPc 1 activity originates in the proton electromagnetic cyclotron instability that occurs when the high‐energy tail of the ring current is brou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
(8 reference statements)
3
20
0
Order By: Relevance
“…Of particular interest is the longer lag and better correlation for the occurrences during a higher range of AE (Figure 5c). This lag agrees well with that observed for pPc 1 versus Dst after intense magnetic storms [Heacock and Akasofu, 1973] and seems to be related to the higher occurrence frequency of substorms during the first several days of recovery of intense storms. The better correlation for this case could also be related to the closer proximity of the subcleft lines to Bar I for that range of AE (the cleft tends to move equatorward with increasing AE [ Yasuhara et al, 1973]).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of particular interest is the longer lag and better correlation for the occurrences during a higher range of AE (Figure 5c). This lag agrees well with that observed for pPc 1 versus Dst after intense magnetic storms [Heacock and Akasofu, 1973] and seems to be related to the higher occurrence frequency of substorms during the first several days of recovery of intense storms. The better correlation for this case could also be related to the closer proximity of the subcleft lines to Bar I for that range of AE (the cleft tends to move equatorward with increasing AE [ Yasuhara et al, 1973]).…”
Section: Discussionsupporting
confidence: 90%
“…According to Kennel and Petschek's [1966] theory, waves can be expected if there is a sufficient flux of energetic protons with suitable proton pitch angle anisotropy and if the total plasma density (cold, warm, plus hot) is high enough to bring the energetic protons to their stable trapping limit. We think that these conditions may be satisfied in the outer plasmasphere during the later part of the ring current recovery phase [Heacock and Akasofu, 1973]. Unfortunately, satellite measurements have not yet defined the plasma structure beyond the plasmapause in sufficient detail to permit a corresponding conclusion for the Bar I unstructured Pc 1-2 events.…”
Section: Discussionmentioning
confidence: 95%
“…The micropu isat ion event discussed here is similar to the periodically structur ed Pc 1 micropulsations described by Heacock and Akasofu [1973] and Mullen and Heacock [1972). Those authors show that structured Pc 1 micropulsations occur during the late recovery …”
Section: Discussionsupporting
confidence: 66%
“… Manchester and Fraser [1970] studied the horizontal propagation of Pc1 signals in the ionospheric duct: Maximum signal attenuation in the duct occurred in midday‐afternoon hours when the E region electron density was maximum, and minimum attenuation occurred near 0500 LT. Heacock and Kivinen [1972] noted the attenuation of Pc1–Pc2 signals toward higher latitudes, and suggested that ionospheric disturbances (such as spread F) associated with storm and/or substorm activity would rather effectively scatter and attenuate Pc1 waves propagating poleward in the ionospheric duct. Heacock and Akasofu [1973] noted that the amplitudes of Pc1 events at sites very near the geomagnetic poles, Thule and Vostok, were almost always quite small, and attributed any amplitude variations to variations in propagation conditions in the F layer waveguide rather than variations in the distance to the source region.…”
Section: Discussionmentioning
confidence: 99%